Correspondence between the Syrian Patriarch of Antioch and the Holy See in the last decade of the seventeenth century - Hasan, Samee (Études sur la Région Méditerranéenne, 2022)
The research aims at elaborating the establishment of the Syrian catholic church and its status in the Levant in the last decade of seventeenth century depending on various manuscripts sent by the Catholic Patriarch of Antioch to the Holy See of Rome and its representative in Constantinople. The manuscripts written in Arabic depict the status of the church in the Ottoman Empire, and its relationship to the European authority including France and Spain. On the other hand, the manuscripts describe set of events related to the relation between the Syrian catholic church and its sister, the orthodox Syrian church and the attitude of the Ottoma Empire toward them.